Mini Review : Metode Floating Treatment Wetland Untuk Pengolahan Air Limbah Penatu - Dwiegi Safitri Febriani; Lita Darmayanti; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The existence of laundry has a positive impact on the community but actually has a negative impact on the environment. Chemical compounds contained in laundry water such as surfactants, can trigger eutrophication in water bodies. If this is allowed continuously will cause water pollution problems. Floating Treatment Wetland (FTW) comes as an option that can be used to decompose water pollutants by utilizing macrophyte plants. This research aims to describe the application of FTW as one of the potential methods for laundry wastewater treatment because it is minimally costly, environmentally friendly, and sustainable.Keywords : Laundry wastewater, FTW, water pollution.